Neurophysiological correlates of religious coping to stress: a preliminary EEG power spectra investigation. (29th May 2020) - Imperatori, Claudio; Bersani, Francesco Saverio; Massullo, Chiara; Carbone, Giuseppe Alessio; Salvati, Ambra; Mazzi, Giorgia; Cicerale, Greta; Carrara, Alberto; Farina, Benedetto
Highlights: The neurophysiological correlates of religious coping to psychological stress have been investigated by means of qEEG. Religious coping was positively associated with theta power in right frontal and temporal areas. The results contribute to increase the knowledge on the neurophysiological concomitants of religious coping to stress. Religious coping was positively associated with other adaptive coping strategies. Abstract: Religious coping to psychological stress has been linked to positive outcomes on both physical and mental health, but no studies have explored its neurophysiological correlates. Ninety-six participants (43 men and 53 women, mean age: 22.30 ± 2.48 years) were enrolled in the present study; they underwent an evaluation of coping with the brief version of the Coping Orientation to Problems Experienced (brief-COPE) scale and performed an eyes-closed resting state electroencephalographic (EEG) recording. EEG analyses were conducted with the exact Low-Resolution Electromagnetic Tomography software (eLORETA). Positive correlations between religious coping and EEG activity were observed in the theta frequency band in the right hemisphere, specifically in the superior temporal, inferior frontal, and middle temporal gyri. Religious coping scores were significantly positively associated with active coping and positive reframing coping strategies, with the latter not being significantly associated with EEG data. Taken together our results contribute to increase the knowledge on the neurophysiological concomitants of religious coping to stress.